The use of the Excellence of Google Assistant for Smart Room Monitoring and Control - Riska Rahma Ramadhani Nasution; Suroso Suroso; Eka Susanti (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
The development of technology in modern times is increasingly sophisticated, so as to create a tool that facilitates human work in operating these electronic goods. When you want to travel far and for a long time, there are often omissions due to forgetting to turn off electronic items such as lights and fans. This does not save the cost of electricity bills and is of course very detrimental. This research was conducted to create a utilization of the advantages of Google Assistant for monitoring and controlling smart rooms. The use of Google Assisstant is very easy if you want to control electronic devices at one time and especially at a very long distance. The electronic devices used in this study were headlights, RGB lights, rice cookers, humidifiers and DC fans. The results of this research can control the lights, rice cooker and humidifier remotely, the fan turns on at a predetermined speed according to the temperature in the room and there is a timer to turn the lights on and off automatically so that it greatly facilitates human work.